2009
DOI: 10.1002/pen.21593
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for single fiber tensile test of natural fibers

Abstract: An improved Single Fiber Tensile Test (SFTT) for the natural fibers was depicted. Natural fibers have irregular shape, and are not uniform along the fiber length and also from one fiber to another. Applying the conventional method, which determine the fiber cross‐section by measuring the fiber diameter using optical microscopy, will result in inaccurate properties of the natural fibers with large standard deviation (SD). In the proposed new SFTT method, an accurate cross‐section area could be obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…Polarized optical microscope images showed the structure of hemp fibres to contain series of dislocations [25]. Sawpan et al [28] also observed the kinks in the structure Adhesive covering the fibre (the pulled-out region)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polarized optical microscope images showed the structure of hemp fibres to contain series of dislocations [25]. Sawpan et al [28] also observed the kinks in the structure Adhesive covering the fibre (the pulled-out region)…”
Section: Introductionmentioning
confidence: 99%
“…It is usually determined either through density measurement and backcalculation of the fibre fineness/diameter [25], or through direct measurement along the gauge length from microscope images, or measuring the diameter at the point of failure [25,26]. The problem with the first method is that it is not accurate as it depends on the apparent density and that with the latter is that it assumes the fibre to be of circular cross-section, which is rarely the case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers invariably use the longitudinal tensile modulus (which is always higher than the transverse modulus) of NFs to predict the mechanical behavior of NFRPCs. However, some researchers who considered this approach defective resorted to using the Young's modulus from a bundle of NFs for predicting the performance of NFRPCs [38] [39]. Both approaches still have their associated drawbacks owing to the anisotropic properties of NFs [40].…”
Section: Tensile Testmentioning
confidence: 99%
“…Before SEM observation, the samples were coated with Au/Pd to ensure good conductivity. For SFTT, the tensile properties of fl ax fi bers were evaluated according to the procedure described in [12] .…”
Section: Sem Observationmentioning
confidence: 99%